2002
DOI: 10.1038/modpathol.3880534
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Variability in the Diagnosis of Ulcerative Colitis-Associated Dysplasia by Telepathology

Abstract: Telepathology (TP) is the practice of remote diagnostic consultation of electronically transmitted, static, digitalized images. The diagnostic efficacy of TP-based consultation services has not been widely tested. Dysplasia that arises in association with chronic ulcerative colitis (CUC) is, at present, the most important marker of an increased risk of malignancy in patients with this disease. Unfortunately, dysplasia is difficult to diagnose histologically and, as a result, suffers from a significant degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
12

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(79 citation statements)
references
References 19 publications
1
66
0
12
Order By: Relevance
“…This system consists of 4 categories-negative for dysplasia, IND, LGD, and high-grade dysplasia-with an overall fair and modest interobserver agreement for negative for dysplasia and high-grade dysplasia, and poorer agreement (higher variability) for LGD and IND. [97][98][99] The IND category is used when the epithelial changes cannot be classified as either negative or positive for dysplasia with certainty. For example, IND may be rendered when coexisting florid acute inflammation, lack of the surface epithelium for evaluation, or processing/technical issues preclude definitive assessment of the epithelial alterations.…”
Section: Terminologymentioning
confidence: 99%
“…This system consists of 4 categories-negative for dysplasia, IND, LGD, and high-grade dysplasia-with an overall fair and modest interobserver agreement for negative for dysplasia and high-grade dysplasia, and poorer agreement (higher variability) for LGD and IND. [97][98][99] The IND category is used when the epithelial changes cannot be classified as either negative or positive for dysplasia with certainty. For example, IND may be rendered when coexisting florid acute inflammation, lack of the surface epithelium for evaluation, or processing/technical issues preclude definitive assessment of the epithelial alterations.…”
Section: Terminologymentioning
confidence: 99%
“…This is most prominent in nongastrointestinal specialized pathologists and between the classification of marked regenerative changes versus low grade dysplasia and between the classification of high grade dysplasia and invasive adenocarcinoma (Riddell et al, 1983). Interobserver studies show only moderate levels of agreement between pathologists' interpretations (Dixon et al, 1988;Eaden et al, 2001b;Melville et al, 1989;Odze et al, 2002). The levels of agreement were lowest in cases of indefinite dysplasia and low grade dysplasia.…”
Section: Interobserver Variability In Grading Of Dysplasiamentioning
confidence: 99%
“…These limitations are mainly related to static telepathology-based consultations, which can be largely overcome by the use of whole-slide imaging with much higher-resolution pictures. 28 The diagnostic accuracy of telepathology The diagnostic accuracy of telepathology, as compared with routine glass slides, is still a matter of 28 reported that in cases of dysplasia with ulcerative colitis, the level of agreement of digital images was slightly lower than that obtained after reviewing the original glass slides. However, this study used static selective fields for consultation.…”
Section: Telepathology: Applications and Limitationsmentioning
confidence: 99%